Importance of intraspecific variation in the pollination and seed dispersal functions of a double mutualist animal species. Issue 1 (31st October 2019) - Fuster, Francisco; Traveset, Anna
Abstract : Although most plants depend on different animals for pollination and seed dispersal, sometimes the same animal species provides both functions, being thus involved in what has been termed a 'double mutualism'. Very little is known on the effectiveness of such species as both pollinators and seed dispersers, and even less on the intraspecific level differences at the contribution of an animal mutualist to plant fitness. In this study, we focused on the interaction between a Mediterranean shrub Cneorum tricoccon (Rutaceae) and the Balearic lizard Podarcis lilfordi (Lacertidae) in order to assess: 1) the role of this lizard as a legitimate pollinator of the plant (previously thought to be exclusively insect‐pollinated), and 2) the intraspecific variation in the use of flowers and fruits by lizard individuals, comparing males, females and juveniles. We further evaluated whether lizards show different fruit size selection depending on sex and age, with potential consequences for seed germination. Lizards visited more flowers and selected more hermaphrodite flowers than insects did, leading to relative increases in both fruit and seed set. Interestingly, female and juvenile lizards were the main flower visitors, whereas males were the main fruit consumers. Males selected the largest fruits (bearing the largest seeds) though this did not increase seed germination, which was only ca 15%. We concluded that P. lilfordi acts as a legitimate pollinator of C. tricoccon and, thus, confirm that this system constitutes a new case of double mutualism, especially common in island compared to mainland systems. Moreover, our findings show a large variation among conspecific individuals in their role as either pollinators or seed dispersers, with potential implications for plant reproductive success. Our study, therefore, highlights the importance of evaluating plant–animal interactions at the intraspecific level, and calls for more in‐depth studies on the consequences of such intraspecific variation.